IMPLEMENTASI PEMBUKUAN KEUANGAN DIGITAL DAN PEMANFAATAN APLIKASI ACCURATE ONLINE UNTUK WIRAUSAHAWAN MUDA PADA BUMDES “TUNAS HARAPAN” DI DESA GERAK MAKMUR - Agustyawati, Dwi; Hidayatullah, Muh.; Suherman, Ansar; Al Zarliani, Wa Ode; Murni, Wa Ode; Rahma Baadi, Tiya (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This Community Service Program aims to improve the financial management of BUMDes “Tunas Harapan” through the implementation of digital bookkeeping using Accurate Online. The program employed initial observation, basic accounting training, application training, implementation assistance, and monitoring and evaluation. The results indicate improved understanding of digital financial recording, enhanced ability to prepare structured financial reports, and the establishment of a more transparent and accountable financial administration system. Additionally, the digitalization of bookkeeping increased efficiency and strengthened data-based decision-making among the management team. This program contributes to institutional capacity building and serves as a model for digital financial systems in rural communities.